Blockchain-Based Medical Record Management System (BBMRMS) - Yi, Chong Hao; Keong, Lee Kim; Razali, Nurul Farhaini (Journal of Applied Technology and Innovation, 2023)
BBMRMS is a system that can increase the security of electronic medical records with cryptographic and decentralized techniques. The system is designed using Java programming language on the Apache NetBeans platform. The immutable characteristics of blockchain technology, which cannot be changed subsequently, are appropriate for medical records that should be non-editable. Furthermore, BBMRMS can also increase the interoperability of medical records between different healthcare facilities and reduce the risk of exchanging medical records electronically with the traceability and transparency features provided by blockchain technology. Hyperledger Fabric Framework has been implemented to deploy a consortium blockchain network for BBMRMS.